Analisis Konsentrasi Industri dan Profitabilitas Industri Air Minum dan Air Mineral dalam Kemasan di Indonesia: Studi Kasus 1990-2014 - Az-Zahra, Maisa Az-Zahra (PT Literasi Nusantara Publisher, 2024)
The food and beverage industry stand as a highly potential sector in Indonesia, contributing significantly to the country's Gross Domestic Product (GDP) in the non-oil and gas manufacturing sector, with a notable 7% contribution in 2004. Specifically, the bottled water and mineral water industry within this sector plays a crucial role as a staple commodity. This research aims to analyze the concentration of the bottled water and mineral water industry, covering businesses involved in packaged drinking water, natural mineral water, demineralized water, and refillable water in Indonesia. The study investigates market structure and explores the relationship between industry concentration and the price-cost margin (PCM) in the bottled water and mineral water industry in Indonesia. The findings indicate that this industry falls within the medium to lower category, demonstrating a market structure of monopolistic competition or loose oligopoly. Moreover, a positive and significant relationship is identified between PCM and Concentration Ratio (CR4) as well as Herfindahl-Hirschman Index (HHI).